Effect of ketoconazole on the pharmacokinetics of a single oral dose of mefloquine in healthy volunteers - Nantida Raungsri (Prince of Songkla University, 2004)
Thesis (M.Sc., Pharmacology)--Prince of Songkla University, 2004